A propensity-matched analysis of surgery and stereotactic body radiotherapy for early stage non-small cell lung cancer in the elderly. Issue 52 (December 2016) - Wang, Peng; Zhang, Dong; Guo, Xue-Guang; Li, Xiao-Mei; Du, Le-Hui; Sun, Bao-Jun; Fang, Xiang-Qun; Guo, Ying-Hua; Guo, Jun; An, Li; Qu, Ge-Ping; Liu, Chang-Ting
Abstract : Abstract: Elderly patients with early stage non-small cell lung cancer (NSCLC) who undergo surgical resection are at a high risk of treatment-related complications. Stereotactic body radiation therapy (SBRT) is considered an alternative treatment option with a favorable safety profile. Given that prospective comparative data on SBRT and surgical treatments are limited, we compared the 2 treatments for early stage NSCLC in the elderly. We retrospectively collected information from the database at our geriatric institution on patients with clinical stage IA/B NSCLC who were treated with surgery or SBRT. The patients were matched using a propensity score based on gender, age, T stage, tumor location, pulmonary function (forced expiratory volume in 1 second [FEV1]% and FEV1), Charlson comorbidity score, and World Health Organization performance score. We compared locoregional control rate, recurrence-free survival (RFS), overall survival (OS), and cancer-specific survival (CSS) between the 2 treatment cohorts before and after propensity score matching. A total of 106 patients underwent surgery, and 74 received SBRT. Surgical patients were significantly younger (72.6 ± 7.9 vs 82.6 ± 4.1 years, P  = 0.000), with a significantly higher rate of adenocarcinoma ( P  = 0.000), better Eastern Cooperative Oncology Group performance scores ( P  = 0.039), and better pulmonary function test results ( P  = 0.034 for predicted FEV1 and P  = 0.032 for FEV1). In an unmatched comparison, there were significant differences in locoregional control ( P  = 0.0012) and RFS ( P  < 0.001). The 5-year OS was 69% in patients who underwent surgery and 44.6% in patients who underwent SBRT ( P  = 0.0007). The 5-year CSS was 73.9% in the surgery group and 57.5% in the SBRT group ( P  = 0.0029). Thirty-five inoperable or marginally operable surgical patients and 35 patients who underwent SBRT were matched to their outcomes in a blinded manner (1:1 ratio, caliper distance = 0.25). In this matched comparison, the follow-up period of this subgroup ranged from 4.2 to 138.1 months, with a median of 58.7 months. Surgery was associated with significantly better locoregional control ( P  = 0.0191) and RFS ( P  = 0.0178), whereas no significant differences were found in OS (5-year OS, 67.8% for surgery vs 47.4% for SBRT, P  = 0.07) or CSS (67.8% for surgery vs 58.2% for SBRT, P  = 0.1816). This retrospective analysis found superior locoregional control rates and RFS after surgery compared with SBRT, but there were no differences in OS or CSS. SBRT is an alternative treatment option to surgery in elderly NSCLC patients who cannot tolerate surgical resection because of medical comorbidities. Our findings support the need to compare the 2 treatments in randomized controlled trials.